Agronomic and economic contrasts between monocrop maize and associated maize/bean systems - Francis, C.A.; Flor Montoya, Carlos A.; Prager Mosquera, Martín (International Center for Tropical Agriculture, 1975)
A large proportion of the maize planted in the tropics and highlands of Latin America is associated with beans and other crops. Agronomic research generally has focused on the improvement of varieties and hybrids, and the development of systems and technology for monoculture. The high production potential of associated maize/bean cropping systems indicate that they should receive more attention in future research in the tropics. One of the important results in 1975 was the confirmed observation that maize does not suffer yield reduction when associated with beans. When the appropriate system is determined for each region, including density of planting, relative planting dates, and physical organization of the two crops in the field, there is sometimes an increase in maize production in these complex systems. It has been concluded that the land efficiency ratio (LER) is twenty to eighty percent greater in associated cropping compared to monoculture of either crop. Highest production and gross income are achieved with the monocrop climbing beans under high technology. Nevertheless, production costs are high. Net income in associated cropping systems almost always surpasses that of monocultures when the cost of labor and materials is high. These complex associated cropping systems have been developed by the farmer under certain climatic, resource, economic and cultural constraints. A better understanding of the system will allow the researcher to develop new technological alternatives to increase production potential, net income and nutriton for the small farmer in the tropics.